Realization of Spanish vowels by native speakers and Polish immigrants - Waluch de la Torre, Edyta (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This article aims to describe the phenomena that characterize Poles as speakers of peninsular Spanish (specifically in its Granada’s variation) in their pronunciation of vowels. The analysis bases on surveys collected in the non-bilingual adult Polish population residing in Granada for more than 10 years. The investigation includes the representation and the phonetic and acoustic comparison of the vowels in their most complexes contexts. The study describes the different ways of vowel performance in Spanish by Polish immigrants. The conclusions reveal the degree of its phonetic assimilation in specific cases, as well as the parameters influencing its null adjustment, partially or totally akin to the native vowel pronunciation.